Follow the Feeling - Wright, Kai (Ascent Audio, 2019)
In Follow the Feeling, strategy advisor Kai D. Wright answers a critical question plaguing entrepreneurs, brand strategists, marketers, and leaders: how do you grow your brand in a noisy world? Analyzing 1,500 fast-growing companies from Alibaba to Zara, the Columbia University lecturer and Ogilvy global consulting partner unpacks five branding secrets. Starting with behavioral economic principles and ending with a new systems-based approach to brand building, Wright offers listeners one metric that trumps the hundreds entangling brand value, feelings. Follow the Feeling will show you how to best build and position your brand so you can stand out from competitors, build a tribe, and engineer a positive feeling across five important branding territories-lexicon, audio cues, visual stimuli, experience, and culture. Through storytelling, global research, and practical tips, this valuable book will help you and your organization efficiently create and deploy a comprehensive brand strategy across the organization; quickly launch new brands or reboot existing brands for growth; build tribes from audiences, consumers, clients, and partners; and lean into the convergence of communication, culture, digital, and technology.